Effects of an educational playful intervention on nasal hygiene behaviors of preschoolers: a quasi-experimental study - Priscila Costa; Talita Ermini; Cecilia Helena de Siqueira Sigaud (Health Promotion Perspectives, 2019)
Background: To determine the effects of an educational playful intervention on nasal hygiene behaviors among preschool (3-4 years old) children. Methods: A quasi-experimental before-after study was conducted with 39 children attending public daycare center in Sao Paulo, Brazil. A group-based intervention consisted of two educational sessions to promote healthy behaviors for nasal hygiene. It was adopted playful strategies such as a story told by puppets, card games and simulation of nasal hygiene in front of the mirror. The outcome was evaluated by observing six healthy behaviors for nasal hygiene one week before and after the intervention. Differences in the outcome before and after the intervention were tested using Wilcoxon signed rank test and McNemar’s test. Results: The median of healthy nasal hygiene behaviors went from 3.0 to 4.0 after the intervention, with a significant statistical difference (P=0.0004) and a difference of behaviors. After the intervention, forcing the air out of one opened nostril increased from 5.1%to 30.8% (P=0.001, CI 95%: 0-0.440), forcing the air out of the other nostril increased from 5.1% to 28.2% (P=0.003/CI 95%: 0-0.50), throwing the piece of toilet paper in the garbage increased from 53.8% to 87.21% (P=0.04, CI 95%: 0.035-0.65), and sanitizing the hands with soap and water increased from 15.4% to 43.6% (P=0.039-0.76). Conclusion: the educational playful intervention improved the autonomy of preschoolers to adopt healthy nasal hygiene behaviors.